Answer:
The resultant expression is [tex]2x^{2}+5x^{2}-x-6[/tex].
Step-by-step explanation:
The distributive property of multiplication is:
[tex]a\times (b+c)=(a\times b)+(a\times c)[/tex]
The two polynomials provided are:
[tex](2x+3)\\(x^{2}+x-2)[/tex]
Determine the final expression by multiplying the two polynomials as follows:
[tex](2x+3)\times (x^{2}+x-2)=[2x\times(x^{2}+x-2)]+[3\times(x^{2}+x-2)][/tex]
[tex]=[(2x\times x^{2})+(2x\times x)-(2x\times 2)]+[(3\times x^{2})+(3\times x)-(3\times 2)]\\\\=[2x^{3}+2x^{2}-4x]+[3x^{2}+3x-6]\\\\=2x^{3}+2x^{2}+3x^{2}-4x+3x-6\\\\=2x^{3}+5x^{2}-x-6[/tex]
Thus, the resultant expression is [tex]2x^{2}+5x^{2}-x-6[/tex].